2003
DOI: 10.1258/096914103771773267
|View full text |Cite
|
Sign up to set email alerts
|

The quality of routine examinations of the newborn performed by midwives and SHOs; an evaluation using video recordings

Abstract: Objective:To evaluate the quality of the routine examination of the newborn as carried out by senior house of cers (SHOs) and midwives.Design: Randomised controlled trial set in a district general hospital in Southeast England. Eligible babies were randomised to a midwife (11) or an SHO (8) who were then video recorded undertaking the routine newborn examination. Main outcome measures:Quality of 62 observed technical and communication components of the newborn examination, as agreed between independent consult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 16 publications
0
22
0
Order By: Relevance
“…Study limitations include a single centre design, and the absence of a validated method for assessment of newborn examination skills 26. While we demonstrated that the provision of additional learning material had a positive impact on the newborn examination skills of medical students, a randomised controlled trial comparison of the module with another additional learning resource would provide stronger evidence for the benefit of the module itself.…”
Section: Discussionmentioning
confidence: 75%
“…Study limitations include a single centre design, and the absence of a validated method for assessment of newborn examination skills 26. While we demonstrated that the provision of additional learning material had a positive impact on the newborn examination skills of medical students, a randomised controlled trial comparison of the module with another additional learning resource would provide stronger evidence for the benefit of the module itself.…”
Section: Discussionmentioning
confidence: 75%
“…In another study, midwives specifically trained in the newborn examination were compared with SHOs given no specific training using video recordings to evaluate the quality of the newborn examination. 249 When rated by a consultant paediatrician masked to the identity of the examiner, a similar percentage of cardiac screening examinations performed by midwives and SHOs were rated as appropriately completed. When rated by a senior midwife, SHOs performed significantly worse than midwives.…”
Section: Effectiveness Of Current Uk Policymentioning
confidence: 99%
“…Clinical screening for DDH relies on detection of hip subluxation or dislocation soon after birth using Barlow or Ortolani methods and is experience-dependent with skilled, trained and experienced operators more reliably performing the procedure [6, 7]. As few as 31% of cases of DDH diagnosed on Graf ultrasound have a history of recognised risk factors or positive findings on clinical examination [8, 9].…”
Section: Introductionmentioning
confidence: 99%